2022
DOI: 10.48550/arxiv.2206.12677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marginal $T\bar{T}$-Like Deformation and ModMax Theories in Two Dimensions

Abstract: Recently, the ModMax theory has been proposed as a unique conformal nonlinear extension of electrodynamics. We have shown in [1] that this modification can be reproduced a marginal T T -like deformation from pure Maxwell theory. Further, this deformation is solved by using a perturbative approach. In this letter, we will investigate another ModMax-like deformation for a two-dimensional (2D) scalar field theory. In this regard, we first find a marginal T T -like deformation in two dimensions and then reproduce … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Thus, eq. ( 3.3) precisely agrees with the flow that has been recently considered in [32,33] and [34] (see also [35,36]), for some concrete examples in the Lagrangian formalism. Indeed, in [32] it was shown that a dimensional reduction of the ModMax theory [38] (see also [39][40][41][42]) to two spacetime dimensions corresponds to the continuous √ T T deformation of N = 2 free bosons, and then extended the deformation to arbitrary N .…”
Section: √ T T Deformationssupporting
confidence: 85%
See 3 more Smart Citations
“…Thus, eq. ( 3.3) precisely agrees with the flow that has been recently considered in [32,33] and [34] (see also [35,36]), for some concrete examples in the Lagrangian formalism. Indeed, in [32] it was shown that a dimensional reduction of the ModMax theory [38] (see also [39][40][41][42]) to two spacetime dimensions corresponds to the continuous √ T T deformation of N = 2 free bosons, and then extended the deformation to arbitrary N .…”
Section: √ T T Deformationssupporting
confidence: 85%
“…The deformation of free bosons was also addressed in [33] from a more general approach, where it was argued that the deformation should also work well for a wider class of examples, as confirmed in [36]. The same result for free bosons was also obtained in [34] from a perturbative approach. Later on, in [35] it was shown that the flow equation (3.2) in Lagrangian form can be reduced to a set of first order non-linear PDE's by the method of characteristics, and applied them to recover the deformation of free bosons.…”
Section: √ T T Deformationsmentioning
confidence: 68%
See 2 more Smart Citations
“…The T T deformation of gauge fields has also been studied in connection with DBI-like theories[28][29][30].…”
mentioning
confidence: 99%